2012
DOI: 10.1002/stem.1094
|View full text |Cite
|
Sign up to set email alerts
|

Human Epithelial Basal Cells Are Cells of Origin of Prostate Cancer, Independent of CD133 Status

Abstract: Normal prostatic epithelium is composed of basal and luminal cells. Prostate cancer can be initiated in both benign basal and luminal stem cells, but because basal cell markers are not expressed in patient tumors, the former result was unexpected. Since the cells of origin of prostate cancer are important therapeutic targets, we sought to provide further proof that basal stem cells have tumorigenic potential. Prostatic basal cells were enriched based on a2b1integrin hi expression and further enriched for stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
65
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 38 publications
5
65
0
Order By: Relevance
“…Our findings that basal cells are efficient cells of origin for human prostate cancer are consistent with previous findings by our group and others (15,16). These studies on the human disease have all used a tissue-regeneration approach to model development concomitant with tumorigenesis.…”
Section: Cd49fsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings that basal cells are efficient cells of origin for human prostate cancer are consistent with previous findings by our group and others (15,16). These studies on the human disease have all used a tissue-regeneration approach to model development concomitant with tumorigenesis.…”
Section: Cd49fsupporting
confidence: 92%
“…Naïve human prostate basal cells can initiate acinar-type adenocarcinoma in response to oncogenic stimulation (15). Consistent with these findings, basal cells from the BPH-1 human prostate cell line can initiate human prostate cancer in response to combined estrogen and testosterone treatment (16). These collective data suggest that human prostate tumors may set aside a subset of basal cells within the tumor to ensure continuous production of malignant luminal-like cancer cells.…”
supporting
confidence: 60%
“…8 94 A recent report has shown that recombination of cancer-associated fibroblasts with integrin α2β1 hi human prostate basal cells (from non-tumorigenic BPH-1 cells) regenerates tumor grafts. 95 In summation, these results suggest that both human and murine prostate basal cells can serve as cells-of-origin for PCa.…”
Section: Pcscsmentioning
confidence: 83%
“…Downregulation and hypermethylation of DAH genes are not associated with tumourigenic induction of prostate epithelial cells. To understand whether the downregulation and hypermethylation of DAH genes are strictly associated with prostate tumour formation, BPH-1 cells were recombined with either normal prostate fibroblasts (NPF -inducing normal growth) or cancer-associated fibroblasts (CAFinducing tumour formation) and grafted in the renal capsule of NOD-SCID mice 41 ( Figure 6a). BPH-1 þ CAF tumours exhibit squamous-like differentiation and do not express AR in their epithelial component.…”
Section: Ar Protein Was Found Only In Rare Cells (Supplementarymentioning
confidence: 99%